A sociolinguistic analysis of bilingual puns in the linguistic landscapes of Guangzhou, China - Peng, Junhua; Mansor, Nor Shahila; Mohd Kasim, Zalina; Ang, Lay Hoon (De La Salle University, 2023)
Punning, either monolingual or bilingual, is a significant action in creating literal humor and rhetorical jokes. Notwithstanding, there is a dearth of linguistic studies on punning, particularly bilingual punning. Therefore, this study aims to conduct a sociolinguistic appraisal of Chinese-English bilingual puns in Guangzhou, an international Chinese metropolis, by presenting and analyzing the data collected from the linguistic landscapes of Guangzhou. A qualitative method was employed in analyzing the data collected from 18 commercial signages with visible bilingual puns that were located in two popular commercial centers of Guangzhou. Resultantly, Chinese-English puns largely occurred at the word level with bilingual homophones as the core of the puns on Guangzhous commercial signage. The wide use of the word Fun showed the conventionalized, context-dependent, and intertextuality features of bilingual puns. Furthermore, bilingual puns displayed an emerging feature of translanguaging in the public space. Hence, this study sheds light on the features of Chinese-English bilingual puns and contributes to existing literature by discovering the sociolinguistic dynamics of bilingualism in Chinese communities.